Antineoplastic Activity of Alkylaminolapachol Analogues and their Copper Complexes against MDA-MB-231 Human Breast Cancer Cell Lines - Pawar, O.B.; Sanas, K.V.; Patwardhan, R.B.; Waghmode, S.A.; Khaladkar, M.Y. (Asian Journal of Chemistry, 2020)
In present study, three alkylamino substituted hydroxynaphthoquinone analogues of naturally occurring bioactive lapachol are synthesized. Further, copper(II) complexes of these ligands have been synthesized using hassle free modified grindstone method. Both ligands and copper(II) complexes were characterized using UV-visible spectroscopy, FTIR, elemental analysis and NMR spectra. Cell viability assay of the compound was carried out against growth of MDA-MB-231 human breast cancer cell lines. A better tumorocidal activity was observed for ligands and their copper(II) complexes in concentration of 2.95 to 0.11 mmol/L. Antineoplastic activity of copper(II) complexes was found to be more than parent ligands. Antimicrobial assay results showed that compound exhibit better activity against organisms under study. Antimicrobial susceptibility of compounds was carried out against culture of E. coli K12 (RP4), B. subtilis (pUB110), K. pneumoniae and S. paratyphi. The lowest MIC of < 0.20 mg/mL was obtained for L-3 against S. paratyphi. Cyclic voltammetry of ligand and complexes performed in non-aqueous system shows that ligand exhibits classical two step redox couple corresponds to the formation of semiquinone and catechole moieties in solution state at characteristic potential values. Whereas cyclic voltammogram of copper(II) complexes exhibit additional peak at characteristic potential corresponds to reversible redox reaction of central Cu(II) ion in complexes.